Characteristics of Plybamboo made from woven mat of Andong Bamboo (Gigantochloa pseudoarundinaceae) - Ega P Yoga; Sukma S Kusuma; Jajang Suryana; Muhammad Y Massijaya (Masyarakat Peneliti Kayu Indonesia, 2014)
The objective of this research was to analyze the influence adhesive types, composition of width and thickness of bamboo strips to the physical and mechanical properties of plybamboo. Keywords: andong bamboo, epoxy, plybamboo. PVAc